Brief Intervention to Reduce Problem Drinking in College Students With ADHD. Issue 3 (August 2019) - Vasko, John M.; Meinzer, Michael C.; Murphy, James G.; Oddo, Lauren E.; McCauley, Katherine L.; Rooney, Mary E.; Lejuez, Carl W.; Chronis-Tuscano, Andrea
Abstract: Despite gaining admission to college, many students with attention-deficit/hyperactivity disorder (ADHD) struggle to achieve academic, social, and occupational success. Additionally, college students with ADHD experience higher rates of problem drinking and comorbid psychology (e.g., depression). This paper describes the development of the Students Understanding College Choices: Encouraging and Executing Decisions for Success (SUCCEEDS) program for college students diagnosed with ADHD who are engaging in problem drinking. SUCCEEDS combines ADHD psychoeducation, behavioral activation, and brief motivational intervention treatment elements to help college students with ADHD achieve healthier and more fulfilling lifestyles. SUCCEEDS aims to decrease problem drinking by increasing substance-free, goal-directed behavior allowing for success in college. The iterative treatment development process, two SUCCEEDS illustrative case examples, and reliable change indices are presented. Preliminary results suggest that SUCCEEDS may be effective in reducing problem drinking and functional impairment in areas relevant to college students (e.g., academics). Highlights: SUCCEEDS combines ADHD psychoeducation, BA, and MI treatment elements. SUCCEEDS was developed with UCC and SHC input to enhance dissemination potential. Two case examples illustrate the implementation of SUCCEEDS. Case examples decreased total weekly drinks and impairment in various domains. Preliminary evidence shows SUCCEEDS beneficial for college students with ADHD.